Penyisihan Zat Organik, Warna Dan Besi (Fe) Pada Pengolahan Air Gambut Secara Koagulasi Dan Flokulasi Dengan Menggunakan Koagulan Alami Dari Biji Jagung (Zea Mays L.) - Firdha Ozani Rosselda Fahmi; Dewi Fitria; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Peat water in Riau Province may be a source of clean water because of its availability, but the quality still does not meet the quality standards of clean water according to Minister of Health Regulation No. 32 of 2017, such as organic substances, colors and Fe still high. One method that can be used to remove contaminants in peat water is the coagulation and flocculation process using natural coagulant corn seeds. This study aims to determine the effect of coagulant dose of corn seeds and slow stirring speed in removing organic matter, color and Fe in peat water by varying the coagulant dose of dosis 5 mg/L; 10 mg/L; 15 mg/L; 20 mg/L; 25 mg/L and 30 mg/L The results obtained showed that the highest Fe removal was found at a coagulant dose of 80 mg/L with an efficiency of 61.12%, while for organic substances and colors it did not meet the quality standards. Key words: Coagulation and Flocculation, Peat Water, Corn seeds, Organic Substance, Color and Fe